Gambaran Empati Generasi Milenial di Pekanbaru - Fadhillah, Qori'ah (Journal of Islamic and Contemporary Psychology, 2021)
Empathy is an individual ability to identify and understand about people’s feelings, so a person can see and feel other people’s feelings from many perspectives without losing control of themselves. The purposes of this research is to know about Empathy of Millenials Generation in Pekanbaru. It was a descriptive analytical statistic that involves 145 participants, which uses disproportionate stratified random sampling technique and Interpresonal Reactivity Index (IRI) scale that contains 20 items. The result shows that Millenial Generation in Pekanbaru have empathy in a medium range or average percentage 31,7% from 46 participants. There are significant differences between each age range (significancy score = 0,014, p < 0.05), the average score in 25-29 years old is the highest than other age range. There are no significant differences of averages empathy score based on gender, spare time, and language. We can conclude that Millenial Generation in Pekanbaru is not good enough in understanding other people’s feeling and put themselves up to other people.